Analisis Pengaruh Karakteristik Reviewer terhadap Niat Beli: Pendekatan Interaksi Parasosial - Chandra Suparno; Dafi Andin Robbi Muhammad (Annusfy : Journal of Multidisciplinary Research, 2026)
This study examines how social attractiveness, perceived similarity, and trustworthiness influence purchase intention, mediated by parasocial interaction. Adopting a case study design, data were collected from 203 active Instagram followers of Indonesian reviewer Fadil Jaidi using purposive sampling and analyzed via Structural Equation Modeling (SEM) with AMOS. The results indicate that perceived similarity and trustworthiness positively affect parasocial interaction, which subsequently drives purchase intention. Furthermore, parasocial interaction significantly mediates the relationships of perceived similarity and trustworthiness with purchase intention. Conversely, social attractiveness has no significant effect on purchase intention and is not mediated by parasocial interaction. These findings underscore the critical role of psychological ties between reviewers and followers in shaping consumer purchase behavior on social media platforms.